Numerical analysis of low-frequency electromagnetic field effects from three-phase transformer on coronary stents and cardiac tissues - Rui Tian; Jia-Yi Luo; Mai Lu; Jing-Jing Cui (PLoS ONE, 2026)
The widespread clinical adoption of novel magnesium alloy coronary stents, combined with increasing densification of urban power transmission infrastructure, highlighted a significant research gap regarding the effects of power-frequency electromagnetic fields (EMFs) on these implants. This study employed field-circuit coupling numerical methods to simulate electromagnetic field exposure in simulated patients with implanted coronary stent positioned at various locations near a 200kVA three-phase transformer. The analysis focused on the distribution patterns of induced electromagnetic fields within both cardiac tissues and the stent, as well as the resultant Ampere forces acting on the stent. The results showed that the simulated patient directly beneath the three-phase transformer was exposed to the maximum electromagnetic radiation, but the magnetic flux density ( B max ) and the induced electric field intensity ( E max ) of the cardiac tissue were lower than the public exposure limits of the International Commission on Non-Ionizing Radiation Protection (ICNIRP). The B max and E max of the stent at the same position were 1.245 μ T and 5.086 × 10 −4 mV/m, respectively. The maximum Ampere force density of the stent in the Y- axis (perpendicular to the coronal plane) was 3.714 × 10 −6 N/m 3 . The above findings indicate that, under the conditions of this simulation, a 200 kVA power transformer exerts minimal interference on the magnesium alloy stent and cardiac tissues. The magnetic flux density and induced electric field in the heart tissues, as well as the Ampere force acting on the magnesium alloy stent, all remain within established safety limits.